Prolapse of the urethral mucosa in a prepubertal Indian girl - Pulavarthi, Sabita; Vijayan, Sharmila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Prolapse of urethral mucosa in prepubescent girls is an uncommon entity and most often seen among native Africans. Management of these cases is controversial. Some would adopt initial medical treatment and others prefer surgical treatment as primary modality with a very few recurrences. Though urethral mucosal prolapse has been managed successfully with surgery in many African girls, the role of medical management and its success cannot be overlooked. Authors present a case of urethral mucosal prolapse in a prepubescent Indian girl who was successfully treated with medical management with no recurrence on follow up.